Eco-compatible biochar mitigates volatile fatty acids stress in high load thermophilic solid-state anaerobic reactors treating agricultural waste. (August 2020) - Meng, Lingyu; Xie, Li; Suenaga, Toshikazu; Riya, Shohei; Terada, Akihiko; Hosomi, Masaaki
Highlights: Volatile fatty acids (VFAs) were accumulated in reactors with low inoculum. Methane generation and VFAs degradation were promoted with biochar addition. Carbon dioxide utilization was promoted by either inoculum or biochar addition. Methane yields from soured reactors increased with inoculum or biochar addition. Abstract: A high concentration of accumulated volatile fatty acids (VFAs) is one of the most important factors resulting in reactor failure during solid-state anaerobic digestion. In this study, the feedstock-to-inoculum (F/I) ratio (0.5, 2, 3, 4 and 6) and the recovery method after failure (biochar addition or inoculum addition) were investigated in batch solid-state anaerobic digestion fed with rice straw and pig urine. An F/I ratio of 3 was the threshold for stable operation, while the reactors failed at F/I ratios of 4 and 6 because of high accumulated VFAs concentrations (above 30 g HAc/kg). Biochar addition (10% or 20% (wet weight) of the mixture) was as effective as inoculum addition (by adjusting the F/I ratio to 2 or 3) in promoting VFAs degradation in failed reactors within a short period (<1 day). The buffering capacity of biochar was important in promoting VFAs degradation.